Revised evolutionary relationships within Brachycera and the early origin of bicoid in flies. - Mulhair, P.O.; Pennati, A.; Herrera-Ubeda, C.; Holland, P.W.H. (Current Biology, 2025)
The specification of the anterior-posterior axis in the embryo is a crucial step in early insect development. Despite its importance, the underlying genetic and regulatory architecture controlling this process varies significantly between species. In cyclorrhaphan flies, such as Drosophila melanogaster, anterior determination is controlled by the transcription factor bicoid, which emerged through duplication of the ancestral Hox3 gene (called zen in insects). With new, high-quality genomic data, we mine the genomes of 186 dipteran species and find the presence of bicoid in non-cyclorrhaphan flies, including bee flies (family Bombyliidae) and stiletto flies (Therevidae). We confirm maternal expression and localization of the non-cyclorrhaphan bicoid mRNA to the anterior region of the unfertilized oocyte in the dark-edged bee fly, Bombylius major. To determine the timing and origin of bicoid, we address uncertainty in the dipteran phylogeny, uncovering a ladder-like topology in the branching orders of the early Brachycera lineages. This new species phylogeny suggests that bicoid emerged in the common ancestor of Bombyliidae, Asiloidea, and Eremoneura (collectively Heterodactyla) and was subsequently lost at least 16 times. These findings expand our understanding of early developmental processes in flies and provide new insights into the backbone phylogeny of Diptera and the evolution of bicoid.